Procedura powoływania i odwoływania wiceprezesów Najwyższej Izby Kontroli a gwarancje ich niezależności — wnioski de lege lata i postulaty de lege ferenda - Wolanin, Mikołaj (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
In the article, the author deliberates whether the procedure of appointing and dismissingvice-presidents of Polish Supreme Audit Office (SAO, NIK) is both de iure and de facto independent from the Polish executive and any other institutions which can be controlled by the SAO. That is why the author describes the procedure of appointing and dismissing the vice-presidents of the SAO and, through de lege lata conclusions, tries to point out possible threats to the full independence of the procedure itself as well as the specific persons participating in this procedure. The analysis takes into account constitutional conditions of the Polish political system and how — for example — the Polish Government is appointed. Noticing the threats, the author proposes de lege ferenda to introduce into law legal solutions aiming to minimize the possibility of the governing party (parties), among other entities, influencing the described procedure.
Keywords: Polish Supreme Audit Office; NIK (SAO); vice-presidents of NIK; independence of NIK; constitutional law; state control; institutions of the state control